Examining the role of training design, supervisor support, peer support, and motivation in facilitating training transfer in a Malaysian public sector context - Mat Nazir, Eliy Nazira; Ariffin, Zuritah; Mohamad, Mutiiah; Kamaruddin, Sharir Aizat; Mohd Fauzi, Shukor Sanim (Universiti Teknologi MARA, Perlis, 2025)
The purpose of this quantitative research is to examine the extent to which various factors influence the transfer of training within a Malaysian public sector organization, and whether these factors provide advantages or disadvantages to employees. Specifically, the study investigates four key variables: training design, supervisor support, peer support, and motivation to transfer. Data were collected through structured questionnaires distributed to 124 male and female employees who regularly participate in training programs within the organization. The questionnaires were carefully designed to capture relevant insights related to the transfer of training. The findings indicate a positive relationship between training design, supervisor support, peer support, and motivation to transfer. However, out of the four independent variables tested, only peer support and motivation to transfer were found to significantly influence the actual transfer of training. These results suggest that interpersonal and motivational factors play a more substantial role in training transfer than the structural elements of training or supervisory involvement. Ultimately, this study aims to enhance understanding of training effectiveness by identifying the most influential factors in promoting successful training transfer within the public sector.